2020
DOI: 10.3390/antibiotics9080450
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Mechanisms of Flavonoids against the Emerging Opportunistic Nontuberculous Mycobacteria

Abstract: Nontuberculous mycobacteria (NTM) are the causative agent of severe chronic pulmonary diseases and is accountable for post-traumatic wound infections, lymphadenitis, endometritis, cutaneous, eye infections and disseminated diseases. These infections are extremely challenging to treat due to multidrug resistance, which encompasses the classical and existing antituberculosis agents. Hence, current studies are aimed to appraise the antimycobacterial activity of flavonoids against NTM, their capacity to synergize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 209 publications
(270 reference statements)
1
15
0
Order By: Relevance
“…1). The findings of this study coincide with that described by the literature for propolis, since phenolic acid has been identified as the main classes of secondary metabolites extracted in propolis ethanolic and the antimicrobial activity may be due to the action of the phenolic compounds detected (Lavinas et al 2019;Machado et al 2016), being appointed as responsible for inhibit NTM growth in previous studies by Mickymaray et al (2020) and Przybyłek & Karpiński (2019).…”
Section: Resultssupporting
confidence: 91%
“…1). The findings of this study coincide with that described by the literature for propolis, since phenolic acid has been identified as the main classes of secondary metabolites extracted in propolis ethanolic and the antimicrobial activity may be due to the action of the phenolic compounds detected (Lavinas et al 2019;Machado et al 2016), being appointed as responsible for inhibit NTM growth in previous studies by Mickymaray et al (2020) and Przybyłek & Karpiński (2019).…”
Section: Resultssupporting
confidence: 91%
“…The mechanism of antimicrobial activity of polyphenols against bacteria can differ and also depends both on the polyphenol type and bacteria species. Among the most important mechanisms of the antibacterial action of polyphenols are [ 58 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]: Reactions with proteins; Inhibition of nucleic acid synthesis by bacterial cells or DNA damage; Interaction with the bacterial cell wall or inhibition of cell wall formation; Alteration of cytoplasmic membrane function, such as modifications of the membrane permeability or fluidity, cytoplasmic membrane damage and—in the result—the membrane disruption; Inhibition of energy metabolism; Changes in cell attachment and inhibition of biofilm formation; Substrate and metal deprivation. …”
Section: Mechanism Of Antibacterial Activity Of Polyphenolsmentioning
confidence: 99%
“…Fatty acid synthase II (FAS-II) is a key enzyme for the synthesis of fatty acids building the bacterial membranes. It catalyzes fatty acid chain elongation, from 16–24 carbons obtained de novo by FAS-I to long-chain fatty acids of 36–48 carbons as well as mycolic acids [ 92 ]. Flavonoids such as isoliquiritigenin (142) , butein (144) , fisetin (107) and 2,2′,4′-trihydroxychalcone (139) inhibited FAS-II, thus preventing the growth of Mycobacterium smegmatis [ 119 ].…”
Section: Mechanism Of Antibacterial Activity Of Polyphenolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current research, it was observed that various earthworms possessed proteolytic, lipolytic, amylolytic, and antioxidant activities. erefore, we can say that these bioactive substances (enzymes) and antioxidants may act as an antibacterial agent having various mechanisms/ modes of actions (Figure 2), such as (1) the disruption/alteration/modification of plasma membrane and cell wall structure and function after attachment, (2) interruption of nucleic acid synthesis (DNA replication), (3) inhibition of RNA synthesis (transcription) and their functions, (4) interference with metabolic pathways, (5) inhibition of the protein synthesis and functions, and (6) generation of free radicals to disrupt cell membrane/cell wall, and anchoring to the cell membrane/cell wall [44,[78][79][80]. Our findings also agree with previous studies [81,82].…”
Section: Antioxidant Potential Effectmentioning
confidence: 99%